PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL KOOPERATIF TIPE COURSE REVIEW HORAY DI KELAS IV SDN 17 GUNUNG PANGILUN KOTA PADANG - Muhammad Fathur Ardana; Arwin; Yesi Anita; Inggria Kharisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improvement of fourth-grade students’ learning outcomes in Natural and Social Sciences through the application of the Cooperative Learning model of the Course Review Horay (CRH) type at SDN 17 Gunung Pangilun, Padang City. The study was motivated by the low learning outcomes of student, where only 37% of 19 students reached the minimum mastery criteria in the first-semester daily assessment of the 2025/2026 academic year, caused by teacher-centered, monotonous, and less innovative learning practices. This research employed a Classroom Action Research design following the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 18 fourth-grades student (9 boys and 9 girls) together with the classroom teacher as observer. Data were collected through test and non-test techniques, including teaching-module assessment sheets, teacher and student activity observation sheets, and learning-outcomes tests, then analyzed descriptively using a percentage formula. The result showed that the quality of the teaching module increased from 81.25% (good) in Cycle I to 95.81% (very good) in Cycle II; teacher activity increased from 78.40% to 95.45%; student activity increased from 82.81% to 95.45%; and student’ learning outcomes increased from an average score of 65.31 in Cycle I to 86.77 in Cycle II. These findings indicate that the application of the Course Review Horay model can effectively improve fourth-grade student’ learning outcomes, activeness, and confidence in the IPAS subject.